How do Restructuring Processes Influence Low- and Unskilled Immigrant and Nonimmigrant Workers and their Managers in a Norwegian Hospital? - Enehaug, Heidi; Mamelund, Svenn-Erik (Nordic Journal of Working Life Studies, 2015)
It is a well-known fact that workplace restructuring has undesirable effects on the psychosocial work environment, health, and sick leave, but no attention has been given to the health effects of work environments characterized by restructuring, a multicultural staff, and a strong socioeconomic occupational hierarchy. In this casestudy, we examine a large Norwegian hospital in which all of these features are present. Through in-depth interviews with employees and their managers we investigate the healthiness of the restructuring process, and the consequences of the restructuring process on the work environment, subjective health, and sick leave. Results show that immigrant workers received less information, had higher level of frustration and less control over work, and experienced a decrease in well-being, autonomy, and social support. Immigrant worker vulnerability, that is, the handicap of poor understanding of the Norwegian language and a lack of understanding of general and local organizational norms and practices in the Norwegian workplace, is an important explanation. Immigrant workers with a poor Norwegian language understanding are even worse off. We conclude that a strong occupational hierarchy within the hospital exerts an overall influence on the position of low/unskilled employees in the restructuring process as well as their perception of and involvement in it.